Comparison of metabolic profiles and bioactivities of the leaves of three edible Congolese Hibiscus species. Issue 24 (17th December 2017) - Kapepula, Paulin Mutwale; Kabamba Ngombe, Nadege; Tshisekedi Tshibangu, Pascal; Tsumbu, César; Franck, Thierry; Mouithys-Mickalad, Ange; Mumba, Dieudonné; Tshala-Katumbay, Désiré; Serteyn, Didier; Tits, Monique; Angenot, Luc; Kalenda, Pascal Dibungi T.; et al.
Abstract: Methanolic and dichloromethane extracts from the leaves of Congolese Hibiscus species were characterised by chromatographic and spectroscopic techniques and their in vitro biochemical activities against ROS production were evaluated in cellular models and on an enzyme, myeloperoxidase (MPO), involved in inflammation. Hibiscus acetosella has a chemical fingerprint different from Hibiscus cannabinus and Hibiscus sabdariffa both having similar fingerprints. Major compounds were polyphenols, represented mainly by caffeoyl-hydroxycitric acid for H. acetosella and neochlorogenic acid for the two other species. All extracts displayed high cellular antioxidant activity with IC50 values ranging from 0.5 to 3 μg mL −1 using lucigenin on neutrophils. Dichloromethane extracts showed more efficient effects on extracellular ROS production and MPO activity. Antioxidant and anti-inflammatory activities of caffeoyl-hydroxycitric acid were significantly higher than those of neochlorogenic acid. The bioactivities of Hibiscus species were positively correlated with their phytochemical content and could justify their use as local nutraceutical resources and medicines. Abstract :